TRADE-5G: A blockchain-based transparent and secure resource exchange for 5G network slicing - El-hacen Diallo; Khaldoun Al Agha; Steven Martin (Blockchain: Research and Applications)
The advent of 5G technology has revolutionized network communication by introducing network slicing (NS) and virtualization to allow multiple network service providers (NSPs) to share infrastructure, thereby reducing deployment costs and accelerating 5G adoption. While this new open marketplace enables NSPs to trade resources dynamically, it also exposes the system to security concerns, such as front-running and selfish-validation attacks, which can lead to market manipulation and strategy leakage. This paper presents TRADE-5G, a secure blockchain-based marketplace for 5G resource trading that mitigates these attacks and ensures fair, transparent resource allocation while preserving the confidentiality of NSP strategies. Through extensive simulations, TRADE-5G demonstrates a substantial 18% improvement in user satisfaction and a 36% reduction in wasted resources compared to traditional models. Additionally, it opens new profit opportunities for NSPs through unused resources, establishing a more competitive, secure, and transparent 5G trading environment that exceeds the capabilities of traditional mobile networks.